Hidroxipropilação de amido e fibras de resíduo de açaí para obtenção de biocompósitos - Lopes, Henrique Solowej Medeiros (2025)
Within the context of materials engineering, starch stands out as a sustainable source for the production of biofilms, due to its biodegradability and its renewable source of high produc-tion in several different climates and regions. However, pure starch materials have insuffi-cient properties for their wide application in industry and commerce, and hydroxypropyla-tion is a sustainable way to reduce the hydrophilic and fragile character of the material. In this study, cassava starch and açaí residue were chemically modified by hydroxypropylation. The combination of parameters for sample preparation was performed by a design of exper-iments 2³ full factorial. The substrates were previously activated with KOH in water and ethanol solution, modified in different molar ratios (0.4, 0.6 and 0.8 OHPO/OHglucose), tem-peratures (115, 125 and 135 °C) and açaí residue proportions (0, 5 and 10 wt%). The effects of each defined parameter were evaluated by analysis of variance (ANOVA), revealing that the molar ratio and the higher amount of açaí residue significantly increased the mass gain, while the temperature had the opposite effect. The structural characterization by FTIR and solid-state NMR confirmed the chemical modification through the identification of methyl bond peaks, with quantification of the degree of substitution by elemental analysis and sol-id-state NMR, varying between 0.1 and 0.4, as the molar ratio increases and the temperature decreases. Notably, complete gelatinization of starch was observed during the reaction, evi-denced by the absence of crystalline structures in XRD and SEM. However, homopolymeri-zation of propylene oxide (PPO) has been observed, resulting in the intermolecular presence of PPO in the polymer chains, significantly increasing the plasticization of the material. This plasticization can be observed by TG and DSC, which indicate a reduction in thermal stability, in addition to accelerated retrogradation with the formation of short- and long-range crystalline structures via XRD and FTIR, especially in samples containing açaí resi-due. Due to the previous plasticization of starch, films were obtained via casting at room temperature with significant lower amount of glycerol (7.5% starch weigh basis), resulting in materials with 470% high elongation at break, although with lower maximum tensile strength stress, greater hydrophilicity and tendency to retrogradation. The results demon-strate the potential of chemical modification of starch to expand its applications in sustaina-ble packaging, due to the success in the low use of synthetic plasticizers achieved.